Några vanliga ogräs - Liljander, Paulina (2009)
The Swedish Board of Agriculture initiated this undergraduate thesis. There is a database on their homepage that includes chemical treatments for different weed species. There is also space for preventive and mechanical control methods. This is an undergraduate thesis that reviews these control methods for the most important weeds in Sweden.